A Comprehensive Analysis of the Impact of HIV on HCV Immune Responses and Its Association with Liver Disease Progression in a Unique Plasma Donor Cohort. - Yong-Hong Zhang; Yan Zhao; Ushani S Rajapaksa; Tessa M Lawrence; Yan-Chun Peng; Jinghua Liu; Keyi Xu; Ke Hu; Ling Qin; Ning Liu; Huanqin Sun; Hui-Ping Yan; et al. (PLoS ONE)
Objective Human Immunodeficiency Virus (HIV) and Hepatitis C virus (HCV) co-infection is recognized as a major cause of morbidity and mortality among HIV-1 infected patients. Our understanding of the impact of HIV infection on HCV specific immune responses and liver disease outcome is limited by the heterogeneous study populations with genetically diverse infecting viruses, varying duration of infection and anti-viral treatment. Methods Viral-specific immune responses in a cohort of 151 HCV mono- and HIV co-infected former plasma donors infected with a narrow source of virus were studied. HCV and HIV specific T cell responses were correlated with clinical data. Results HIV-1 accelerated liver disease progression and decreased HCV specific T cell immunity. The magnitude of HCV specific T cell responses inversely correlated with lower HCV RNA load and reduced liver injury as assessed by non-invasive markers of liver fibrosis. HIV co-infection reduced the frequency of HCV specific CD4+ T cells with no detectable effect on CD8+ T cells or neutralizing antibody levels. Conclusion Our study highlights the impact of HIV co-infection on HCV specific CD4+ T cell responses in a unique cohort of patients for both HCV and HIV and suggests a crucial role for these cells in controlling chronic HCV replication and liver disease progression.